The role of melatonin in the development of postmenopausal osteoporosis - Yang, Keda; Qiu, Xueshan; Cao, Lili; Qiu, Shui (Frontiers in Pharmacology, 2022)
Melatonin is an important endogenous hormone that modulates homeostasis in the microenvironment. Recent studies have indicated that serum melatonin levels are closely associated with the occurrence and development of osteoporosis in postmenopausal women. Exogenous melatonin could also improve bone mass and increase skeletal strength. To determine the underlying mechanisms of melatonin in the prevention and treatment of postmenopausal osteoporosis, we performed this review to analyze the role of melatonin in bone metabolism according to its physiological functions. Serum melatonin is related to bone mass, the measurement of which is a potential method for the diagnosis of osteoporosis. Melatonin has a direct effect on bone remodeling by promoting osteogenesis and suppressing osteoclastogenesis. Melatonin also regulates the biological rhythm of bone tissue, which benefits its osteogenic effect. Additionally, melatonin participates in the modulation of the bone microenvironment. Melatonin attenuates the damage induced by oxidative stress and inflammation on osteoblasts and prevents osteolysis from reactive oxygen species and inflammatory factors. As an alternative drug for osteoporosis, melatonin can improve the gut ecology, remodel microbiota composition, regulate substance absorption and maintain metabolic balance, all of which are beneficial to the health of bone structure. In conclusion, our review systematically demonstrates the effects of melatonin on bone metabolism. Based on the evidence in this review, melatonin will play a more important role in the diagnosis, prevention and treatment of postmenopausal osteoporosis.